Craniofacial and cardiac defects in chd7 zebrafish mutants mimic CHARGE syndrome - Sun, Yuhan; Kumar, S. Ram; Wong, Chee Ern David; Tian, Zhiyu; Bai, Haipeng; Crump, J. Gage; Bajpai, Ruchi; Lien, Ching Ling (Frontiers in Cell and Developmental Biology, 2022)
Congenital heart defects occur in almost 80% of patients with CHARGE syndrome, a sporadically occurring disease causing craniofacial and other abnormalities due to mutations in CHD7 gene. Animal models have been generated to mimic CHARGE syndrome; however, heart defects are not extensively described in zebrafish disease models of CHARGE using morpholino injections or genetic mutants. Here we describe the co-occurrence of craniofacial abnormalities and heart defects in zebrafish chd7 mutants; these mutant phenotypes are enhanced in the maternal zygotic mutant background. In chd7 mutant fish, we found shortened craniofacial cartilages and extra cartilage formation. Furthermore, the length of the ventral aorta is altered in chd7 mutants. Many CHARGE patients have aortic arch anomalies. Notably, the aberrant branching of the first branchial arch artery is observed for the first time in chd7 fish mutants. To understand the cellular mechanism of CHARGE syndrome, neural crest cells (NCCs), that contribute to craniofacial and cardiovascular tissues, are examined using sox10:Cre lineage tracing. In contrast to its function in cranial NCCs. we found that the cardiac NCC-derived mural cells along the ventral aorta and aortic arch arteries are not affected in chd7 mutant fish. The chd7 fish mutants we generated recapitulate some of the craniofacial and cardiovascular phenotypes found in CHARGE patients and can be used to further determine the roles of CHD7.